Strategi Keterbukaan Diri Oleh Pendamping kepada Anak-anak Korban Kekerasan Seksual di Surakarta - Azis Arouf; Vinisa Nurul Aisyah (Program Studi Ilmu Komunikasi, 2020)
The purpose of this research is to understanding the strategy of self-disclosure conducted by companion of Yayasan Kakak Surakarta to children’s sexual abuse victim. Self-disclosure by companion to children’s sexual abuse victim be used to resolve case of children’s sexual abuse and rehabilitations process of victim. The type of research is descriptive and qualitative with determine the informant use purpossive sampling. The technique data collection use indepth-interview and observation. Data validity using data triangulation. The results of this research is companion from Kakak Foundation Surakarta has different strategy at each area self-disclosure. Open area, companion use strategy that collaboration with another affairs and sharing tasks between companions from Kakak Foundation based on victim data. Hidden area companion use empathy to rising up the confidence and give pleasent feel for victim to reveal the sexual abuse incident. Blind area companion use strategy give powerfull respons to children’ sexual abuse victim in order to tell the information that in point of fact they don’t know about. Meanwhile in unknown area constitute area that can not be reveal because that is about the victim destiny in the future after the case resolved.